Feminisme Islam dalam Perspektif Raden Ajeng Kartini - Isnawati, Reni; Isnaini, Elsa (Indonesian Journal of Islamic Theology and Philosophy, 2022)
Abstract;Feminism is often seen as a women's injustice movement in an effort to seek justice for women. The status of men and women is the same, but often the status of men is higher than that of women. Islamic feminism emerged because society was unfair in treating women. One of those who fought for feminism in Indonesia was R.A Kartini (1879 – 1904) who was one of the proud national figures of the Jepara people. Her thoughts and hard work for the advancement of women made her recognized as a hero of women's emancipation. Kartini's struggle for feminism gave results that women can feel today, namely being able to pursue education on a par with men in terms of obtaining education. Because of its connection to the rise of feminism in Indonesia, the author is interested in discussing Islamic feminism from the perspective of Raden Ajeng Kartini. This research uses the library research method by using R.A Kartini's work as a primary source. The results of the writing show that in his thoughts regarding education for women it does not conflict with Islamic values. In fact, in a hadith, the Prophet Muhammad said, "Seeking knowledge is the obligation of every Muslim (and Muslim woman)." This Hadith of the Prophet narrated by Al-Thabarani through Ibnu Mas'ud emphasizes that women have the same obligations as men in seeking knowledge.Keywords:Education, Kartini; Islamic Feminims. Abstrak;Feminisme sering kali dianggap sebagai gerakan ketidakadilan perempuan dalam upaya mencari keadilan untuk perempuan. Kedudukan laki-laki dan perempuan sama, namun sering kali derajat laki-laki lebih tinggi dibanding dengan perempuan. Feminisme Islam timbul karena terdapat ketidakadilan masyarakat dalam memperlakukan wanita. Salah satu yang memperjuangkan feminisme di Indonesia adalah R.A Kartini (1879 – 1904) yang merupakan salah satu tokoh Nasional kebanggaan masyarakat Jepara. Pemikiran dan kerja kerasnya untuk kemajuan perempuan membuat beliau diakui sebagai pahlawan emansipasi perempuan. Perjuangan kartini dalam feminisme memberikan hasil yang dapat dirasakan perempuan hingga sekarang, yaitu dapat menempuh pendidikan setara dengan laki-laki dalam hal memperoleh pendidikan. Karena keterkaitannya dalam kebangkitan feminisme di Indonesia, maka penulis tertarik untuk membahas mengenai feminisme Islam dalam perspektif Raden Ajeng Kartini. Penelitian ini menggunakan metode studi pustaka (library research) dengan menjadikan karya R.A Kartini sebagai sumber primer. Hasil penulisan menunjukkan bahwa dalam pemikirannya mengenai  pendidikan bagi kaum perempuan tidak bertentangan dengan nilai Islam. Bahkan dalam sebuah hadisnya, Nabi Muhammad bersabda, “Menuntut ilmu adalah kewajiban setiap Muslim (dan Muslimah).” Hadis Nabi yang diriwayatkan Al-Thabarani melalui Ibnu Mas’ud ini menegaskan, bahwa kaum perempuan memiliki kewajiban yang sama dengan kaum laki-laki dalam menuntut ilmu pengetahuan.Kata Kunci:   Feminisme Islam; Kartini; Pendidikan.